APPLICATION OF A NUMERICAL-ANALYTIC METHOD TO BOUNDARY VALUE PROBLEMS FOR INTEGRO-DIFFERENTIAL EQUATIONS OF VOLTERRA TYPE WITH NONLINEAR BOUNDARY CONDITIONS - Nurzhanov, O.D.; Nurzhanov, B.O. (SCIENCE and SOCIETY, 2026)
In this work, a boundary-value problem for systems of Volterra-type integro-differential equations with nonlinear boundary conditions is investigated using the numerical-analytic method of successive approximations.
Keywords: boundary-value problem; numerical-analytic method; Volterra-type integro-differential equations; nonlinear boundary condition